2021
DOI: 10.1080/17461391.2020.1867650
|View full text |Cite
|
Sign up to set email alerts
|

Predicting middle‐distance track and cross‐country performances of national and international level adolescent runners

Abstract: This study evaluated the contribution of physiological data collected during laboratory testing in predicting race performances of trained junior middle-distance track (TK) and cross-country (XC) athletes. Participants performed a submaximal incremental ramp test, followed by an incremental test to exhaustion in a laboratory, with the results used to predict either 800 m TK, 1500 m TK or 4000-6000 m XC race performance. Twenty-eight participants (male (M), 15; female (F), 13) were analysed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Bulbulian et al (11) found that anaerobic work capacity tasks were of greater significance than V̇ o 2 max in predicting XC meet performance in an NCAA Division I men's team similar to the male subjects in this study. Although the study by Bulbulian et al (11) was performed with male runners, it is possible that the shorter distance and higher relative intensities of the female runners during competition further diminished the importance of V̇ o 2 max despite past opposing findings of well-trained youth XC runners (9,13).…”
Section: Discussionmentioning
confidence: 99%
“…Bulbulian et al (11) found that anaerobic work capacity tasks were of greater significance than V̇ o 2 max in predicting XC meet performance in an NCAA Division I men's team similar to the male subjects in this study. Although the study by Bulbulian et al (11) was performed with male runners, it is possible that the shorter distance and higher relative intensities of the female runners during competition further diminished the importance of V̇ o 2 max despite past opposing findings of well-trained youth XC runners (9,13).…”
Section: Discussionmentioning
confidence: 99%